2015
DOI: 10.1080/13102818.2015.1040454
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of American foul brood disease of honeybee in north-west Pakistan

Abstract: American foul brood (AFB) disease is a deleterious bacterial disease worldwide, caused by spore forming bacterium Peanibacillus larvae that affects honeybee larvae and causes a significant decrease in the honeybee population. Following symptomatical and bacteriological approaches combined with 16S rDNA sequencing, an assessment has been made to evaluate the presence of AFB disease in North-West Pakistan as no record for bee-associated bacterial disease from Pakistan is available. A total of 1276 samples from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…The prevalence (1.7 %) of P. larvae in honeybee colonies and (3.03 %) in apiaries recorded in this study is comparatively much lower than that reported in some Asian countries e.g. 37.3 % in honeybee colonies in Pakistan (Anjum et al 2015 ), 24.8 % in honey samples from Taiwan (Chen et al 2008 ) and some European countries e.g. 11 % in Belgium (de Graaf et al 2001 ), 66 % in France (Mouret et al 2013 ) and 5.3–9.8 % in Latvian apiaries (Chauzat et al 2014 ; Laurent et al 2015 ).…”
Section: Discussioncontrasting
confidence: 71%
“…The prevalence (1.7 %) of P. larvae in honeybee colonies and (3.03 %) in apiaries recorded in this study is comparatively much lower than that reported in some Asian countries e.g. 37.3 % in honeybee colonies in Pakistan (Anjum et al 2015 ), 24.8 % in honey samples from Taiwan (Chen et al 2008 ) and some European countries e.g. 11 % in Belgium (de Graaf et al 2001 ), 66 % in France (Mouret et al 2013 ) and 5.3–9.8 % in Latvian apiaries (Chauzat et al 2014 ; Laurent et al 2015 ).…”
Section: Discussioncontrasting
confidence: 71%
“…A. mellifera is one of them, that improved quantities and Qualities of crops through pollination in the selected study areas and have a key role in honey agro-food chain (Munawar et al, 2009). Honey has become one of the most commercial agricultural products for trade in Pakistan since few years (Waghchoure and Martin, 2009, Adnan et al, 2014, Anjum et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The research conducted in the Hatay and Adana Provinces of Turkey has shown that the prevalence of AFB disease was 29% [ 27 ]. The prevalence of AFB disease of honeybee in north-west Pakistan was 37.30% [ 28 ]. Haddad et al .…”
Section: Discussionmentioning
confidence: 99%